The Canonical Discriminant Model of the Environmental Security Threats - Olha Kovalchuk; Mikolaj Karpinski; Ludmila Babala; Mykhailo Kasianchuk; Ruslan Shevchuk (Complexity)
The existence of modern humanity directly depends on environmental security. Human society, biodiversity, ecosystems, and climate safety are interdependent. The anthropogenic influence that causes irreversible climate change threatens both the ecosystem’s existence and humans’ survival. To maintain a balance between human well-being and a safe environment, it is important to have a diverse knowledge of the interrelations between the technological impact on the natural environment and climate change and an understanding of action strategies to mitigate climate change and ensure sustainable development. Applying a scientific approach, data analytics, and data science tools can effectively support climate change mitigation and prevent a climate disaster. Based on the components of the climate change performance index (CCPI) 2023 for 59 countries and the EU, a canonical discriminant model was built to identify the significant factors that influence the assessment of the effectiveness of climate protection in a particular country or region and the assessment of climate risks. It can be used to assess the level of climate protection effectiveness of countries that have not defined the CCPI 2023. Based on empirical data, we have determined the real weights of the relevant CCPI components in relation to the effectiveness of actions aimed at reducing global warming. We have established that there are additional factors important for assessing climate protection, but the CCPI rating does not consider them. We conducted a comparative analysis of the CCPI index and the sustainable development goals (SDG) index. The study establishes that the differences in environmental protection among the world’s countries do not determine the assessment of the level of sustainable development of the world’s countries. The obtained results can provide information to support decision-making in developing effective strategies and urgent actions to ensure climate protection.